WHY DO INTERNATIONAL PATIENTS COME BACK? AN S-O-R EXPLANATION OF SERVICE QUALITY, TRUST, AND SATISFACTION IN SAUDI HOSPITALS - Alruwaili, Khalid; Al-haimi, Basheer; Infante-Moro, Alfonso; Alenzi, Salman (Veredas do Direito, 2026)
Medical tourism has become an increasingly competitive global industry, prompting healthcare destinations to focus on service excellence and long-term patient retention. Using the Stimulus–Organism–Response (SOR) framework, this study examined how service quality (stimulus) affects revisit intentions in Saudi hospitals, with patient satisfaction and trust as organism factors. Service quality is defined as a second-order construct comprising key aspects of healthcare service delivery. A quantitative research approach was adopted, with data collected from international patients in Saudi hospitals, yielding 220 samples. The model was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that service quality has a strong, significant positive impact on both patient satisfaction and trust. Although satisfaction positively influences revisit intention, trust has an even greater effect, highlighting its vital role in shaping patients’ future behaviors in healthcare settings with high perceived risk. The findings confirm the SOR-based mechanism in which service quality serves as a core stimulus, influencing patients’ internal evaluations and subsequent willingness to revisit. This research contributes to the healthcare and medical tourism literature by empirically validating a comprehensive SOR-based model and emphasizing the importance of trust in maintaining patient relationships. In practice, these insights are valuable for healthcare policymakers and hospital managers in Saudi Arabia, especially in light of Saudi Vision 2030, by highlighting the need to improve service quality and to build trust to enhance patient loyalty and international competitiveness.